2001
DOI: 10.1021/jo015884z
|View full text |Cite
|
Sign up to set email alerts
|

Noncommunicating Photoreaction Paths in Some Pregna-1,4-diene-3,20-diones

Abstract: The photochemistry of three pregna-1,4-diene-3,20-diones bearing a hydroxy or alkoxy group at C(17) (4-6) has been examined. Irradiation at 254 or 366 nm, where absorption by the cross-conjugated ketone moiety in ring A is predominant or exclusive, causes the 'lumiketone' rearrangement of this chromophore in low to medium quantum yield (Phi(r) 0.05 to 0.31). On the contrary, irradiation at 310 nm, where the isolated ketone at C(20) absorbs a large portion of light causes Norrish-I fragmentation of that chromop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…This lead to a different photochemistry observed by the direct excitation of ketone chromophore. Albini et al 8,9) have demonstrated non-communicating reaction paths in some pregna-1,4-diene-3,20-dione. Since many steroidal drugs are commonly used and several reports on their phototoxic effects have been reported, [10][11][12][13] it was of interest to extensively study the aspect of competition between chemical reactions of the separated excited moieties incorporated in the rigid skeleton of the steroids.…”
mentioning
confidence: 99%
“…This lead to a different photochemistry observed by the direct excitation of ketone chromophore. Albini et al 8,9) have demonstrated non-communicating reaction paths in some pregna-1,4-diene-3,20-dione. Since many steroidal drugs are commonly used and several reports on their phototoxic effects have been reported, [10][11][12][13] it was of interest to extensively study the aspect of competition between chemical reactions of the separated excited moieties incorporated in the rigid skeleton of the steroids.…”
mentioning
confidence: 99%
“…The exact mechanism of photohemolysis caused by the betamethasone esters could not be confirmed; however, strong inhibition by GSH and BHA, and a minor role of NaN 3 , probably support the involvement of free radical intermediates in this process . The generation of free radical intermediates has already been reported in these compounds (Ricci et al, 2001). GSH, BHA, and NaN 3 are among the more commonly used, well-established scavengers in photohemolysis studies (Vergas et al, 2003;Ray et al, 2006;Schroder and Surmann, 2006).…”
Section: Photohemolysismentioning
confidence: 94%
“…Systemically, they are mainly indicated for the treatment of rheumatoid arthritis (Bernard and Parker, 2001) and allergic manifestations, such as asthma (Schimmer and George, 2007), whereas, topically, they are extensively used in the management of dermatoses, such as psoriases, contact and atopic dermatitis, discoid lupus erythematosis, and other dermatological disorders (Micheal and Rokea, 1997;Dollerey, 1999). One of the limiting factors in the use of these drugs may be the phototoxic reactions induced by them (Ricci et al, 2001). Phototoxicity is defined as a toxic response from a substance applied to the body, which is either elicited or increased (apparent at lower dose levels) after subsequent exposure to light, or that is induced by skin irradiation after systemic administration of a substance (OECD, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Second, for hydrocortisone and flurandrenolide the formation of a 17-carboxylic acid in alkaline environment was demonstrated by using O 2 and OH − as reagents (2,3). Other degradation products concern degradation of the A ring (6)(7)(8) or hydrolysis of the acetonide moiety (9). For a water-free environment such as the TCA ointment, it was shown that the 21-aldehyde and 17-carboxylic acid are the main degradation products (10).…”
Section: Introductionmentioning
confidence: 99%